Whose Norms, Whose Prejudice? The Dynamics of Perceived Group Norms and Prejudice in New Secondary School Classes - Váradi, Luca; Barna, Ildikó; Németh, Renáta (Frontiers in Psychology, 2021)
Ethnic prejudice can lead to exclusion and hinder social integration. Prejudices are formed throughout socialization, and social norms inform individuals about the acceptability of prejudice against certain outgroups. Adolescence is a crucial period for the development of intergroup attitudes and young people are especially prone to follow the norms they perceive in their reference groups. At the same time, the effect of perceived norms on prejudice in school classes has been yet rarely studied. In Hungary, where prejudice against the Roma is wide-spread and there is no clear social norm proscribing prejudiced manifestations, this topic is especially relevant. In the present paper, based on multi-level analyses of panel data from Hungarian ninth-graders, we find that adolescents adjust their attitudes to those they perceive to be dominant among their classmates and that classmates serve as more important reference groups than teachers do. More contact with Roma is found to be associated with less prejudice against them. Looking at school classes, we find that at the beginning of the school year, many students underestimate the rejection of prejudiced expressions in their classes. By the end of the year, many students are found to adjust their own attitudes to the falsely perceived class norm. Based on our findings, we argue that school classes should be treated as important normative contexts for the socialization of intergroup attitudes and should receive special attention from both scholars and practitioners working in the fields of prejudice research and reduction. Furthermore, we suggest that teachers can most successfully hinder prejudices by working on a common, visible, shared class norm rather than “teaching” students that prejudices are not acceptable.